'Don't know' responding and estimates of perceived risk: failing to provide a 'don't know' response systematically biases laypeople's perceived risk estimates. (2nd January 2020) - Kiviniemi, Marc T.; Ellis, Erin M.; Orom, Heather; Waters, Erika A.; Hay, Jennifer L.
Abstract : Individuals sometimes report that they don't know their risk for a health problem, but many studies of illness risk perception do not provide a 'don't know' (DK) response option. We examined how providing versus not providing a DK option affected responding – either the number of DK responses when the option was provided or the number of skips when a DK option was not provided. We also examined whether it systematically affected perceived risk estimates. Participants (N = 960) reported perceived absolute and comparative risk for four health issues. They were randomly assigned to receive risk questions with or without a DK response option. In the DK Option condition, 'don't know' answers ranged from 3.5% to 12.7% of responses. For all absolute risk questions, perceived risk was significantly higher in the DK Option condition; all Fs (1, 932) < 3.79, all ps < .05. DK responding was issue-specific; more than 25% of the sample answered DK to at least once, but only 2.7% answered DK to more than half of the items. Substantial use of the DK response option and higher perceived absolute risk estimates were seen when a DK response was provided. These findings have implications for assessing the validity of measured risk estimates, of relations between constructs, and for survey design best practices. In addition, they suggest that DK responses are primarily knowledge-based – that individuals answer DK largely because of lacking sufficient knowledge or health literacy to form a risk perception rather than due to satisficing.